CARING FOR PUERPERIAL MOTHERS THROUGH THE UTILIZATION OF TRADITIONAL HERBS TO OPTIMIZE THEIR HEALTH - Nurina Hasanatuludhhiyah; Danti Nur Indiastuti; Yuani Setiawati; Nurmawati Fatimah (Jurnal Layanan Masyarakat, 2023)
Puerperium is a critical period in which mothers often experience physical and psychological problems, however it is the beginning of the breastfeeding process and determines the success of exclusive breastfeeding. The use of traditional herbs for postpartum mothers is part of Indonesian culture that is starting to be abandoned in urban area. This community service activity aims to increase the knowledge, attitudes and behaviour of the community regarding the importance of postpartum maternal health care and the use of traditional herbs with proper processing methods as a promotive and preventive treatment. This activity was carried out in Gubeng Surabaya District with three stages including preparation, implementation of activities and evaluation. In the preparation stage, a situation analysis was performed. Activities were conducted by delivering lectures, discussions, video demonstrations and training. The evaluation was carried out by obtaining feedback from the social and community empowerment section as well as the pre-test and post-test questionnaires filled out by the participants. Based on the evaluation, the community service can increase participants' knowledge about postpartum health care and lactation management, thereby increasing awareness to play an active role by disseminating information to the community about the importance of family and the neighbourhood support for postpartum and breastfeeding mothers. The participants 'knowledge about the use of traditional medicinal plants for the maintenance of postpartum health and successful breastfeeding also increased, accompanied by an increase in the participants' willingness to prepare traditional jamu from fresh herbal ingredients themselves. This community service needs to be carried out in a sustainable manner with innovative delivery methods.